Probing New Bosons and Nuclear Structure with Ytterbium Isotope Shifts - Door, Menno; Yeh, Chih-Han; Heinz, Matthias; Kirk, Fiona; Lyu, Chunhai; Miyagi, Takayuki; Berengut, Julian C.; Bieroń, Jacek; Blaum, Klaus; Dreissen, Laura S.; Eliseev, Sergey; Filianin, Pavel; et al. (Physical review letters, 2025)
In this Letter, we present mass-ratio measurements on highly charged Yb42+ ions with a precision of 4 ×10−12 and isotope-shift measurements on Yb+ on the 2S1/2→2D5/2 and 2S1/2→2F7/2 transitions with a precision of 4 ×10−9 for the isotopes 168,170,172,174,176Yb. We present a new method that allows us to extract higher-order changes in the nuclear charge distribution along the Yb isotope chain, benchmarking ab initio nuclear structure calculations. Additionally, we perform a King plot analysis to set bounds on a fifth force in the keV/𝑐2 to MeV/𝑐2 range coupling to electrons and neutrons.